Comparative analytical profile of Benincasa hispida thumb. and Cucurbita maxima duchesne - Sheetal Sharma; Anjali Upadhyay; Pramod R Yadav; R Galib; Pradeep Kumar Prajapati (Wolters Kluwer Medknow Publications, 2022)
Background: Cucurbitaceae is a family of health-promoting plants due to their compounds with beneficial effects. This is a family of about 130 genera and about 800 species. Seeds or fruit parts of some cucurbits are reported to possess many therapeutic activities. Benincasa hispida Thumb. familiarly known as Kushmanda and Cucurbita maxima Duchesne as Kashiphala are two varieties of Cucurbitaceae family. Thus, comparative analysis of both these varieties is done to evaluate the analytical profile. Aim: To evaluate the analytical profile of B. hispida and C. maxima. Materials and Methods: Fresh juice, semi-solid, dried powder of both the samples were prepared in the laboratory, and comparative analytical profiles were developed by following standard guidelines of Ayurvedic Pharmacopoeia of India (API). Results and Conclusion: The organoleptic parameters include changes in color, taste, and odor of both samples. In physico-chemical parameters, slight changes in loss on drying, Ph, and Total solid content was mentioned. Total ash value and extractive values have found within the limit as mentioned in API. Phyto-chemical analysis shows the presence of alkaloids, carbohydrates, reducing sugars, flavonoids, and steroids in both varieties. Powder microscopy of both samples showed parenchymatous cells, xylem fibers, xylem tracheid's, epidermal cells, and starch grains which were found sparse in B. hispida and dense in C. maxima. High-performance thin-layer chromatography revealed similarity of 3,4,3 bands at 254 nm and 4,3,4 bands at 366 nm ultraviolet detection in methanolic extract, aqueous, hydro-alcoholic extract, respectively, and fourier-transform infrared spectroscopy study of B. hispida and C. maxima showed the presence of amines, methylene group and alcohols, phenols, and methylene group, respectively.